Urban politics and the urban process - Greenstein, D (1988)
﻿ Both academics and the makers of public policy have for a long time been interested in the study of urban politics, but the subject needs to be integrated with the process of urban growth and development. Too frequently, the urban polity is analyzed as an arena which passively reflects or mechanically responds to more fundamental changes in the urban social structure. In this work, case studies of political reform in Philadelphia at two periods, 1800 to 1854 and 1890 to 1915, develop a number of hypotheses about how the urban polity plays an influential role in shaping the process of urban growth and change. Both case studies begin with computer-assisted analyses of changes in the socio-economic and spatial structures of urban society. Such changes are often considered to be fundamental causes of urban political reform either because they altered political elites' interests in municipal government or because they created enormous new demands on existing municipal works and services. The studies show, however, that social structural changes cannot by themselves explain the course of urban political development in the city of Philadelphia. Concentrating primarily on the formulation and implementation of municipal public works, the studies show that in both periods, the course of political reform was often shaped by two things: the 'private' or selfish interests of political actors, and the fragmented financial, administrative and party structures of the urban polity. More important, the studies show how self-interested political activities, in a polity in which authority was highly fragmented, often had consequences which were far reaching in their impact on the structure and experience of urban life. Indeed, the first case study shows how urban politics shaped the process of social group formation in the industrializing city. The second case study shows how the structure and conduct of urban politics determined social groups' political power in the city. The conclusion then demonstrates how the case studies support a number of hypotheses about the relationship between urban politics and urban society which may be applied generally to analyses of the process of urban growth and change.